2020
DOI: 10.1007/s42972-020-00017-8
|View full text |Cite
|
Sign up to set email alerts
|

Policy Practice Is Important But…Voices of Social Service Departments Directors

Abstract: The purpose of this study is to enhance knowledge about the involvement of social workers in policy practice at social service departments in Israel from the perspective of department directors, as well as to identify the driving and restraining forces for involvement in policy practice. The research is based on a qualitative method. Semistructured interviews were conducted with 13 social service departments' directors. The duration of the interviews was from about 60 to 90 min each. The investigators identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 28 publications
(29 reference statements)
0
1
0
Order By: Relevance
“…The finding that SWs holding administrative positions engage more in policy activities as citizens or professionals than front-line SWs emerged in an early study by Irwin Epstein (1981). Later studies found that SW managers engage more in policy because they have more opportunities, greater expectations and more knowledge and self-efficacy (Makaros et al, 2020). Finally, studies have identified personality traits (Schwartz-Tayri, 2020), gender (Meehan, 2019;Ostrander et al, 2019;Shin, 2020) and ethnicity (Bent-Goodley, 2003;Lane and Humphreys, 2011;Nouman and Azaiza, 2021;Darawshy et al, 2022) as factors that influence SWs' engagement in policy routes.…”
Section: Explanationsmentioning
confidence: 99%
“…The finding that SWs holding administrative positions engage more in policy activities as citizens or professionals than front-line SWs emerged in an early study by Irwin Epstein (1981). Later studies found that SW managers engage more in policy because they have more opportunities, greater expectations and more knowledge and self-efficacy (Makaros et al, 2020). Finally, studies have identified personality traits (Schwartz-Tayri, 2020), gender (Meehan, 2019;Ostrander et al, 2019;Shin, 2020) and ethnicity (Bent-Goodley, 2003;Lane and Humphreys, 2011;Nouman and Azaiza, 2021;Darawshy et al, 2022) as factors that influence SWs' engagement in policy routes.…”
Section: Explanationsmentioning
confidence: 99%